Effects of radiation and eckert number on MHD flow with heat transfer rate near a stagnation point over a non-linear vertical stretching sheet - Fenuga, Olugbenga John; Hassan, Anthony R.; Olanrewaju, Philip Oladapo (Zielona Góra: Uniwersytet Zielonogórski)
This work investigates the effects of radiation and Eckert number on an MHD flow with heat transfer rate near a stagnation-point region over a nonlinear vertical stretching sheet. Using a similarity transformation, the governing equations are transformed into a system of ordinary differential equations which are solved numerically using the sixth order Runge-Kutta method with shooting technique. Tabular and graphical results are provided to examine the physical nature of the problem.
Keywords: MHD flow; heat and mass transfer; radiation; Eckert number stagnation -point; non-linear vertical stretching sheet